'Room of requirement' : the interplay of visual and conceptual space in biblical literature for children - Du Toit, Jaqueline S. (Old Testament essays, 2005)
This article presents preliminary thoughts on the concept of 'a bounded region in space', as described by the cognitive linguists Langacker, Lakoff and Johnson. Some biblical stories transform easier than others to the often perceived more 'simplistic' children's version thereof. This study endeavours to consider the interpretative exchange of meaning between the visually contained image, the simplified textual variant and the canonized (supposedly rigidly contained) original text. The interconnectedness of the visual and verbal text(s) lends children's literature particularly well to an investigation of a conceptualist approach to meaning, considering contradictions in Langacker and Lakoff's positions on the container metaphor. Images, from the Old Testament, of containers on or in water (Noah's Ark [Gn 6:9-9:17]; Moses in the basket [Ex 2:1- 10]; and Jonah in the fish [Jnh 1:1-2:10]) will be utilised for the purpose of analysis.